(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The extensive use of antibiotics leads to an increasing number of antibiotic-resistant pathogenic microorganisms. The development of new antimicrobials is needed for clinical, veterinary, and food applications. Bacteriocins are small peptides with antimicrobial activity ribosomally synthesized by bacteria and could be applied as an alternative to classical antibiotics. In this study, the bacteriocin-like (BLIS) peptide, produced by Staphylococcus xylosus was partially purified and main characteristics (pH, thermal stability, resistance to some protease enzymes and molecular weight) were evaluated. Ammonium sulfate precipitation, acetone extraction and ion-exchange chromatography methods were applied for purification of bacteriocin. The activity of bacteriocin was detected using a well diffusion assay method and the amount of protein concentration was estimated by Lowry method. Molecular weight ( 6 kDa) of purified bacteriocin was determined by sodium dodecyl sulphate polyacrilamide gel electrophoresis (SDS PAGE) method. The highest purification yield (80 %) was obtained using ion-exange chromatography and SP-sepharose as sorbent. The purified bacteriocin remained stable at pH values between 2.0 and 12.0 for 4 h. No decrease in antibacterial activity was estimated after 30 min at 121º C temperature. The purified bacteriocin was resistant to papain, pepsin and trypsin action. The BLIS inhibits a growth of Listeria monocytogenes (93 ± 3.0 %), Bacillus subtilis (85 ± 4.0 %), Pediococcus pentosaceus (79 ± 4.0 %), Staphylococcus aureus (51 ± 5.0 %) and Propionibacterium acnes (70 ± 5 %) up to 24 hours. Such bacteriocin preparation could be applied as antimicrobial agent in medical and food industry.